BMI EATING HABITS AND RELATED FACTORS AMONG STUDENTS OF SAVEETHA DENTAL COLLEGE - A/P Sivakumar, Nathasha; GowriSethu,; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research is to evaluate the BMI and eating habits among students at Saveetha Dental College. The last two decades have witnessed tremendous changes in the eating pattern of the Indian population. There has been a revolution in the adolescent's lifestyles and eating patterns, which can be largely attributed to changes in family and social environment. The changes in eating patterns may adversely affect their health. 100 students of Saveetha Dental College in the age group of 17-26 years were selected for the study and were divided into five age groups, respectively. Age 17-18 (group 1), 19-20 (group 2), 21-22 (group 3), 23-24 (group 4), 25-26 (group 5). The questionnaires were distributed to them, and their food intake for 1 whole week was noted down. The collected data is tabulated for further interpretation of the study. The results were assessed statistically. Almost every fourth male student was overweight. Strikingly 15% of female students were underweight. The highly significant difference was found between the average body mass index (BMI) of male and female students. Students’ BMI did not correlate with average family income or with the frequency of taking breakfast. Increasing the proportion of adolescents meeting recommended dietary and physical activity guidelines has been identified as an important strategy to contrast the epidemic increase in obesity, especially in Western countries. These students are more concerned about their appearance than their healthy diet intake. They are keener on finishing their work than taking proper care of their health.